2023
DOI: 10.3390/antiox12030596
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Phytochemical Screening of Artemisia Species

Abstract: Taking into account the increasing number of antibiotic-resistant bacteria, actual research focused on plant extracts is vital. The aim of our study was to investigate leaf and stem ethanolic extracts of Artemisia absinthium L. and Artemisia annua L. in order to explore their antioxidant and antibacterial activities. Total phenolic content (TPC) was evaluated spectrophotometrically. Antioxidant activity was evaluated by DPPH and ABTS. The antibacterial activity of wormwood extracts was assessed by minimum inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 84 publications
(102 reference statements)
0
3
0
Order By: Relevance
“…The antimicrobial properties of the A. annua extract prepared from cv. Novichok (the Nikitsky Botanic Garden) were comparable to those of the A. annua methanol extracts from India, but they were lower than those of the A. annua methanol extracts from Bulgaria [ 85 , 86 ] and significantly higher than those of the ethanol extracts from the plants grown in Romania [ 87 ]. Among all the species under study, the A. dracunculus ethanol extract demonstrated a selective antimicrobial activity against R. iranicus , requiring the lowest inhibitory and bactericidal concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…The antimicrobial properties of the A. annua extract prepared from cv. Novichok (the Nikitsky Botanic Garden) were comparable to those of the A. annua methanol extracts from India, but they were lower than those of the A. annua methanol extracts from Bulgaria [ 85 , 86 ] and significantly higher than those of the ethanol extracts from the plants grown in Romania [ 87 ]. Among all the species under study, the A. dracunculus ethanol extract demonstrated a selective antimicrobial activity against R. iranicus , requiring the lowest inhibitory and bactericidal concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, Artemisia has shown antibacterial activity against drug-resistant bacterial strains. For example, Artemisia absinthium L. leaf extracts exhibit antibacterial activity against S. aureus [141]. Given the results of our review, we believe that the limited nature of the direct evidence on the antimicrobial activities of Vitex species, when compared to other genera, is due to the fact that Vitex species have been less extensively studied for their antimicrobial properties, and more research is needed to understand their full potential.…”
Section: Discussionmentioning
confidence: 97%
“…A previous study showed that the leaf and stem ethanolic extracts of A. absinthium and A. annua showed significant antibacterial activity against carbapenem-resistant Klebsiella spp., extended-spectrum β-lactamases E. coli (ESBL) and ESBL Klebsiella spp. ( Bordean et al, 2023 ). In our study, the highest antibacterial activity (MIC = 47.5 μg/mL, MBC = 95 μg/mL, IZ = 8 ± 1 mm and 50.5% inhibition of biofilm at 2 MIC concentration) was recorded for WE against S. typhimurium .…”
Section: Discussionmentioning
confidence: 99%